Influence of patient age and comorbid burden on clinician attitudes toward heart failure guidelines - Steinman, Michael A. (2012)
BACKGROUND: Clinical practice guidelines have been criticized for paying insufficient attention to the unique needs of patients with advanced age and multiple comorbid conditions. However, little empiric research is available to inform this topic. METHODS: We conducted telephone interviews with staff physicians and nurse practitioners in 4 VA health care systems. Respondents were asked to rate the usefulness of national heart failure guidelines for patients of different ages and levels of comorbid burden on a five point scale and to comment on the reasons for their ratings. RESULTS: Among 139 clinicians contacted, 65 (47%) completed the interview. Half (49%) were women and 48 (74%) were general internists or family practitioners. On a five-point scale assessing the usefulness of clinical practice guidelines for heart failure, the mean response ranged from 4.4 (+/− 0.7) for patients age <65 years with few comorbidities to 3.5 (+/− 1.2) for patients age >80 years with multiple comorbidities (P<.001). The difference in perceived usefulness varied more by patient age than by the degree of comorbidity (P=.02). Four major concepts underlay the perceived utility of guidelines across different patient types: (a) harms of treatment and patients’ clinical and pharmacologic complexity; (b) expected benefits of treatment; (c) patient preferences and abilities; and (d) confidence in the validity of guideline recommendations. CONCLUSIONS: Clinicians perceive heart failure guidelines to be substantially less useful for patients with older age and greater comorbid burden. Concerns about the clinical and pharmacologic complexity of these patients and the expected benefits of drug therapy were commonly invoked as reasons for this skepticism.